Small Vessel Cerebrovascular Disease: The Past, Present, and Future - Réza Behrouz; Ali R. Malek; Michel T. Torbey (Stroke Research and Treatment)
Brain infarction due to small vessel cerebrovascular disease (SVCD)—also known as small vessel infarct (SVI) or “lacunar” stroke—accounts for 20% to 25% of all ischemic strokes. Historically, SVIs have been associated with a favorable short-term prognosis. However, studies over the years have demonstrated that SVCD/SVI is perhaps a more complex and less benign phenomenon than generally presumed. The currently employed diagnostic and therapeutic strategies are based upon historical and contemporary perceptions of SVCD/SVI. What is discovered in the future will unmask the true countenance of SVCD/SVI and help furnish more accurate prognostication schemes and effective treatments for this condition. This paper is an overview of SVCD/SVI with respect to the discoveries of the past, what is known now, and what will the ongoing investigations evince in the future.